(3QSGdI aj OYhI GdCWHGAs - (3GHf HWdGf , GdeNJGQ Hf GdMSf Hf YHOhf, CHh GdMSf,J (B458 (3g` s
(3ChdgG (B:s
(3cGf di eQjV jgefi CeQg acfJ CdGReg hCSGgQg hCQGUO GdWHjYI ai GfJbGdgG s
(3BNQgG (B:s
(3hYdGLGJgG hGdCOhjI GdfGaYI dgG hGdCYJjGV YeG dGjhLO efgG GdCeQGV hGdG(B>(3hjI ai cejGJgG hjNGda Hjf cjajGJgG s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjI YTQs
(3Jdjg fbhd efgG dQhaS aGFOI GdKhe hYf bUI LGdjfhS eY jHOfG YjSi Ydjg GdSdGes
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B191 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B210s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs